miRNA863-3p sequentially targets negative immune regulator ARLPKs and positive regulator SERRATE upon bacterial infection - Dongdong Niu (Nature Portfolio, 2016)
Small RNA plays an important role in regulating the plant defence against bacterial pathogens. Here the authors propose that miR863-3p acts to fine-tune the timing of defence responses by sequentially silencing negative and positive regulators of the plant immune response.